Gas sensitive material, preparation method thereof, gas sensor and application
By preparing SnO2/MoS2/CNFs gas-sensitive materials, the existing gas sensors have solved the problems of long response time, high working temperature and poor selectivity, and high sensitivity detection and good selectivity to hydrogen are achieved, and are suitable for applications at lower working temperatures.
Patent Information
- Application Number
- CN202411602908.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-11
AI Technical Summary
Existing gas sensors have problems with long response/recovery time, high operating temperature and poor selectivity, which cannot meet the increasingly stringent performance requirements.
Spinning liquid was prepared by mixing polyvinylpyrrolidone, polyacrylonitrile, MoS2 and N,N-dimethylformamide, and nanofiber membranes were obtained by electrospinning. SnO2 nanoparticles were synthesized in situ on the nanofiber membrane by solvothermal method, and finally pre-oxidation and calcination were performed to prepare SnO2/MoS2/CNFs gas-sensitive material.
The gas-sensitive material has high sensitivity and good selectivity to hydrogen at a lower operating temperature (120°C), and the repeated test performance is stable and the error is small.
Smart Images

Figure CN119531041A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of gas sensors, and in particular to a gas-sensitive material and a preparation method thereof, a gas sensor and applications thereof. Background Art
[0002] Lithium-ion battery safety accidents are the primary problem and fatal hidden danger in the development of large-scale energy storage technology. The safety of energy storage lithium-ion batteries has become a bottleneck technical problem that needs to be solved urgently in the process of large-scale promotion and application of energy storage technology. Battery thermal runaway refers to the overheating phenomenon caused by a chain reaction of exothermic reaction inside the battery, which causes a sharp change in the battery temperature rise rate. Accidents of energy storage batteries under extreme conditions such as mechanical damage, electrical abuse, and thermal abuse ultimately manifest in the form of thermal runaway.
[0003] Research has found that the thermal runaway process of LIBs is usually accompanied by a large number of side reactions and the release of gases, among which the main gas types include hydrogen, carbon dioxide, methane, carbon monoxide and ethylene. When thermal runaway develops to a certain stage, the concentrations of gases such as H2, CO2, CH4, C2H4, and CO have increased significantly before entering the smoke stage, especially the detection of H2 is more advanced than the detection of other thermal runaway characteristic gases. This also proves that real-time detection of batteries by gas sensors can achieve early safety warning of battery failures.
[0004] In the field of gas sensors, semiconductor metal oxide nanosheets (MOS) have swept through various market fields at a very fast speed since they were developed due to their high specific surface area and specific crystal interface exposure, attracting widespread attention from countries around the world. However, gas sensors made of MOS have disadvantages such as long response / recovery time, high operating temperature and poor selectivity, which cannot meet the increasingly stringent performance requirements, seriously limiting the further application of semiconductor sensors. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems of long response / recovery time, high operating temperature and poor selectivity of gas sensors in the prior art, and to provide a gas-sensitive material and a preparation method thereof, a gas sensor and applications.
[0006] In order to achieve the above object, the present invention provides a method for preparing a gas-sensitive material, which comprises the following steps:
[0007] (1) mixing polyvinyl pyrrolidone, polyacrylonitrile, MoS2 and N,N-dimethylformamide to obtain a spinning solution;
[0008] (2) obtaining a nanofiber membrane by electrospinning the spinning solution;
[0009] (3) in situ synthesis of SnO2 nanoparticles on the nanofiber membrane using a solvothermal method;
[0010] (4) The SnO2-loaded nanofiber membrane obtained in step (3) is pre-oxidized and then calcined.
[0011] Preferably, in step (1), the concentration of polyvinyl pyrrolidone in the spinning solution is 10 to 40 g / L;
[0012] Preferably, in step (1), the concentration of polyacrylonitrile in the spinning solution is 60 to 80 g / L;
[0013] Preferably, in step (1), the concentration of MoS2 in the spinning solution is 0.3 to 0.8 mol / L.
[0014] Preferably, in step (2), the conditions for electrospinning include: positive voltage of 15 to 20 kV, negative voltage of -1 to -3 kV, flow rate of 0.4 to 0.6 mL / h, temperature of 50 to 70° C., and receiving distance of 10 to 14 cm.
[0015] Preferably, step (3) comprises:
[0016] dissolving a tin salt in an organic solvent to obtain a precursor solution;
[0017] The nanofiber membrane is acidified, then mixed with the precursor solution, and then kept warm at 120-180° C. for 8-12 hours.
[0018] Preferably, in the precursor solution, the concentration of tin salt is 0.5 to 2 mol / L;
[0019] Preferably, the tin salt is SnCl2.2H2O and / or SnCl4.5H2O.
[0020] Preferably, the organic solvent is selected from at least one of ethanol, ethylene glycol and propanol.
[0021] Preferably, the acidification treatment is performed using a mixed acid solution, wherein the mixed acid solution is obtained by mixing concentrated sulfuric acid and concentrated nitric acid.
[0022] Preferably, in step (4), the pre-oxidation conditions include: a temperature of 260 to 300° C. and a time of 20 to 40 minutes.
[0023] Preferably, in step (4), the calcination is a two-stage calcination process, wherein the temperature of the first stage is 230-270° C., and the temperature of the second stage is 520-580° C.;
[0024] Preferably, the heating rate in the first stage is 0.5-3°C / min, and the holding time is 40-80min;
[0025] Preferably, the heating rate in the second stage is 1-3°C / min, and the holding time is 150-200min.
[0026] A second aspect of the present invention provides a gas-sensitive material prepared by the method described above.
[0027] A third aspect of the present invention provides a gas sensor, which includes a gas-sensitive material prepared by the method described above.
[0028] A fourth aspect of the present invention provides the use of the gas-sensitive material prepared by the method described above or the gas sensor described above in hydrogen detection.
[0029] The method provided by the present invention prepares a SnO2 / MoS2 / CNFs gas-sensitive material, which combines SnO2 and MoS2 with high gas recognition ability, and CNFs (carbon nanofibers) with high conductivity, high aspect ratio, large specific surface area and high stability. The gas-sensitive material well maintains the structure of the carbon nanofibers, so the gas-sensitive material has high gas-sensitive performance and good selectivity and repeated stability for hydrogen. For example, the gas sensor made of the gas-sensitive material has a sensitivity of 54.8% to 5000ppm of H2 and a sensitivity of 67.2% to 10000ppm of H2, which is relatively high in sensitivity; the gas sensor can be tested at a relatively low operating temperature (120°C); the performance of the gas sensor after repeated tests is similar, and the error is small, indicating that the gas sensor has good repeated performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 is a scanning electron microscope image of the MoS2 / PVP / PAN nanofiber membrane and gas-sensitive material prepared in Example 1 of the present invention;
[0031] Figure 2 This is a graph showing the resistance response test results of the gas sensor prepared in Example 1 of the present invention to 1000-10000 ppm of H2 at 120°C;
[0032] Figure 3 This is a graph showing the sensitivity test results of the gas sensor prepared in Example 1 of the present invention to 1000-10000 ppm of H2 at 120°C;
[0033] Figure 4 This is a resistance response test result diagram of the gas sensor prepared in Example 1 of the present invention repeatedly tested to 10000 ppm H2 at 120°C. DETAILED DESCRIPTION
[0034] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.
[0035] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0036] In the field of sensors, although semiconductor metal oxide nanosheets (MOS) have high gas recognition capabilities, gas sensors made of a single MOS have disadvantages such as long response / recovery time, high operating temperature, and poor selectivity. Transition metal chalcogenides (TMDs) also have high gas recognition capabilities, but gas sensors made of a single TMD also have disadvantages such as long response / recovery time, high operating temperature, and poor selectivity. The present invention has found that by combining two specific MOS and TMD materials: SnO2 and MoS2, using electrospinning technology, the sensitivity of the material to hydrogen can be greatly improved through the synergistic effect of the two.
[0037] In view of this, the present invention provides a method for preparing a gas-sensitive material, the method comprising the following steps:
[0038] (1) polyvinyl pyrrolidone (PVP), polyacrylonitrile (PAN), MoS2 and N,N-dimethylformamide (DMF) are mixed to obtain a spinning solution;
[0039] (2) obtaining a nanofiber membrane by electrospinning the spinning solution;
[0040] (3) in situ synthesis of SnO2 nanoparticles on the nanofiber membrane using a solvothermal method;
[0041] (4) The SnO2-loaded nanofiber membrane obtained in step (3) is pre-oxidized and then calcined to obtain a SnO2 / MoS2 / CNFs gas-sensitive material.
[0042] The method provided by the present invention first obtains a MoS2 / PVP / PAN nanofiber membrane by electrostatic spinning technology, composites SnO2, MoS2 and CNFs, then synthesizes SnO2 nanoparticles in situ on the nanofiber membrane by a solvent thermal method, and finally performs pre-oxidation and calcination treatment to prepare a SnO2 / MoS2 / CNFs gas-sensitive material. The SnO2 / MoS2 / CNFs gas-sensitive material well maintains the structure of the fiber, and under the joint action of SnO2, MoS2 and CNFs, the gas-sensitive material has high gas-sensitive performance, good selectivity and repeated stability for hydrogen.
[0043] In a preferred embodiment, in step (1), the concentration of polyvinyl pyrrolidone in the spinning solution is 10-40 g / L, more preferably 20-30 g / L, specifically, for example, 20 g / L, 21 g / L, 22 g / L, 23 g / L, 24 g / L, 25 g / L, 26 g / L, 27 g / L, 28 g / L, 29 g / L or 30 g / L.
[0044] In a preferred embodiment, in step (1), the concentration of polyacrylonitrile in the spinning solution is 60-80 g / L, more preferably 70-80 g / L, specifically, for example, 70 g / L, 71 g / L, 72 g / L, 73 g / L, 74 g / L, 75 g / L, 76 g / L, 77 g / L, 78 g / L, 79 g / L or 80 g / L.
[0045] In a preferred embodiment, in step (1), the concentration of MoS2 in the spinning solution is 0.3-0.8 mol / L, more preferably 0.4-0.6 mol / L, specifically, for example, 0.4 mol / L, 0.45 mol / L, 0.47 mol / L, 0.5 mol / L, 0.52 mol / L, 0.55 mol / L or 0.6 mol / L.
[0046] In a more preferred embodiment, in step (1), in the spinning solution, the concentration of polyvinyl pyrrolidone is 20-30 g / L, the concentration of polyacrylonitrile is 70-80 g / L, and the concentration of MoS2 is 0.4-0.6 mol / L. By controlling the concentration of each substance in the spinning solution within the above range, the fiber diameter of the nanofiber membrane obtained by electrospinning is more uniform and free of beading.
[0047] In a specific embodiment, in step (1), the MoS2 is nanosheets exfoliated by a liquid phase exfoliation method, so that the MoS2 nanosheets in the spinning solution are free of agglomeration and are easier to disperse.
[0048] In a preferred embodiment, in step (2), the electrospinning conditions include: positive voltage of 15 to 20 kV, negative voltage of -1 to -3 kV, flow rate of 0.4 to 0.6 mL / h, temperature of 50 to 70 ° C, and receiving distance of 10 to 14 cm. Under the above electrospinning conditions, the diameter of the obtained nanofiber membrane is small and more uniform. The receiving distance refers to the linear distance between the needle and the receiving plate.
[0049] In a specific embodiment, step (3) comprises:
[0050] dissolving a tin salt in an organic solvent to obtain a precursor solution;
[0051] The nanofiber membrane is acidified, then mixed with the precursor solution, and then kept warm at 120-180° C. for 8-12 hours.
[0052] In a preferred embodiment, the concentration of the tin salt in the precursor solution is 0.5-2 mol / L, more preferably 0.5-1.8 mol / L, specifically, for example, 0.5 mol / L, 0.6 mol / L, 0.8 mol / L, 1 mol / L, 1.5 mol / L, 1.7 mol / L or 1.8 mol / L.
[0053] In a preferred embodiment, the tin salt is SnCl2.2H2O and / or SnCl4.5H2O.
[0054] The present invention does not limit the specific selection of the organic solvent, and it can be an organic solvent commonly used in the art. In a specific embodiment, the organic solvent is selected from at least one of ethanol, ethylene glycol and propanol.
[0055] In a preferred embodiment, the acidification treatment is performed using a mixed acid solution, wherein the mixed acid solution is obtained by mixing concentrated sulfuric acid and concentrated nitric acid. Further preferably, the mixed acid solution is obtained by mixing concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 3:1.
[0056] The present invention has no particular limitation on the specific concentrations of concentrated nitric acid and concentrated sulfuric acid, which can be the commonly used concentrated nitric acid and concentrated sulfuric acid in the art. In a specific embodiment, the mass fraction of the concentrated nitric acid is 67-69%, and the concentration of the concentrated sulfuric acid is 18.4 mol / L.
[0057] In a preferred embodiment, in step (4), the pre-oxidation temperature is 260-300°C, specifically, for example, 260°C, 265°C, 270°C, 275°C, 280°C, 285°C, 290°C, 295°C or 300°C.
[0058] In a preferred embodiment, in step (4), the pre-oxidation time is 20 to 40 minutes.
[0059] In a preferred embodiment, in step (4), before pre-oxidation, the process further comprises: washing the SnO2-loaded nanofiber membrane with water and ethanol, and then drying it.
[0060] In the present invention, the calcination is performed under an inert atmosphere, wherein the inert atmosphere may be an argon atmosphere.
[0061] In a preferred embodiment, in step (4), the calcination is a two-stage calcination process, wherein the temperature of the first stage is 230-270°C, and the temperature of the second stage is 520-580°C. By adopting the above calcination process, the nanofiber membrane can be carbonized more evenly, thereby increasing the conductivity of the material.
[0062] More preferably, the heating rate in the first stage is 0.5-3°C / min, and the holding time is 40-80min.
[0063] More preferably, the heating rate in the second stage is 1-3°C / min, and the holding time is 150-200min.
[0064] In a preferred embodiment, the calcination process includes: placing the pre-oxidized nanofiber membrane in a tubular furnace, heating it to 230-270°C at a heating rate of 0.5-3°C / min, calcining it for 40-80 minutes, and then heating it to 520-580°C at a heating rate of 1-3°C / min, and calcining it for 150-200 minutes.
[0065] The present invention also provides a gas-sensitive material prepared by the method described above.
[0066] The present invention also provides a gas sensor, which includes the gas sensitive material prepared by the above method. Since the gas sensor of the present invention adopts the above gas sensitive material, it has at least all the beneficial effects brought by the technical solution of the above gas sensitive material, which will not be described one by one here.
[0067] The present invention does not limit the specific preparation method and structure of the gas sensor, which may be a conventional preparation method and structure in the art. In a specific embodiment, the preparation method of the gas sensor includes the following steps:
[0068] A1. Mix the gas-sensitive material with water and then grind to obtain a slurry;
[0069] A2, coating the slurry on the Au electrode to form an electrode film;
[0070] A3. Aging the electrode containing the electrode membrane at 50-70°C for 45-55h.
[0071] The present invention also proposes the use of the gas-sensitive material prepared by the method described above or the gas sensor described above in hydrogen detection.
[0072] The present invention will be described in detail below by way of examples, but the protection scope of the present invention is not limited thereto. The experimental methods in the following examples, unless otherwise specified, are conventional methods in the art. The experimental materials used in the following examples, unless otherwise specified, are commercially available products.
[0073] Example 1
[0074] (1) Polyvinyl pyrrolidone (PVP), polyacrylonitrile (PAN), MoS2 and N,N-dimethylformamide (DMF) are uniformly mixed to form a spinning solution; wherein, in the spinning solution, the concentration of PVP is 25 g / L, the concentration of PAN is 75 g / L, and the concentration of MoS2 is 0.5 mol / L.
[0075] (2) The spinning solution obtained in step (1) was injected into a 10 mL syringe and electrospun for 24 hours to obtain a MoS2 / PVP / PAN nanofiber membrane; wherein the electrospinning parameters included: positive voltage of +20 kV, negative voltage of -2 kV, flow rate of 0.5 mL / h, needle size of 20 G, temperature of 60 ° C, and receiving distance of 12 cm.
[0076] (3) Concentrated nitric acid and concentrated sulfuric acid were mixed in a volume ratio of 3:1 to obtain a mixed acid solution, and the MoS2 / PVP / PAN nanofiber membrane obtained in step (2) was acidified in the mixed acid solution for 30 minutes.
[0077] (4) Add the weighed SnCl2·2H2O into 25 mL of ethanol solvent and stir evenly to obtain a precursor solution with a concentration of 1 mol / L.
[0078] (5) The precursor solution obtained in step (4) and the nanofiber membrane acidified in step (3) are transferred to a stainless steel reactor with a 50 mL polytetrafluoroethylene liner, and the stainless steel reactor is placed in an oven and heated to 150°C for 10 h. The reaction mixture is then cooled to room temperature and taken out to obtain a nanofiber membrane loaded with SnO2 in situ.
[0079] (6) The in-situ SnO2-loaded nanofiber membrane obtained in step (5) was washed with deionized water and ethanol respectively, dried in an oven at 60°C for 10 h, and then pre-oxidized in a muffle furnace at 280°C for 30 min.
[0080] (7) The pre-oxidized nanofiber membrane in step (6) was placed in a tubular furnace under Ar atmosphere, heated to 250°C at a rate of 1°C / min, calcined for 60 min, and then heated to 550°C at a rate of 2°C / min, calcined for 180 min, to obtain a gas-sensitive material, recorded as SnO2 / MoS2 / CNFs.
[0081] (8) A commercially available flat-plate Au electrode (with extended platinum wire) was cleaned and dried with deionized water and ethanol, respectively. The electrode was provided with a test electrode and a heating electrode. The electrode heating temperature could be controlled by adjusting the input current. The upper surface of the electrode was Au, which was the test end, and the lower surface was Ru, which was the heating end. The overall dimensions of the flat-plate electrode were 1.5×1.5 mm.
[0082] (9) Weigh a certain mass of SnO2 / MoS2 / CNFs into an agate mortar, add deionized water, and the mass ratio of deionized water to gas-sensitive material is 1:1. Then grind it quickly and vigorously until the powder is ground evenly into a paste-like slurry.
[0083] (10) using a brush to evenly apply the slurry obtained in step (9) on the flat Au electrode treated in step (8) to form an electrode film that completely covers the Au electrode;
[0084] (11) The electrode obtained in step (10) is placed on an aging table and aged at 60° C. for 48 h to obtain a gas sensor.
[0085] Example 2
[0086] The method described in Example 1 is used for implementation, except that in step (4), the concentration of SnCl2·2H2O in the precursor solution is 1.8 mol / L.
[0087] Example 3
[0088] The method described in Example 1 is used for implementation, except that in step (4), the concentration of SnCl2·2H2O in the precursor solution is 0.5 mol / L.
[0089] Example 4
[0090] The method described in Example 1 is followed, except that in step (5), the stainless steel reactor is placed in an oven and heated to 130°C.
[0091] Example 5
[0092] The method described in Example 1 is followed, except that in step (5), the stainless steel reactor is placed in an oven and heated to 180°C.
[0093] Comparative Example 1
[0094] The method described in Example 1 is followed, except that in step (1), no MoS2 nanosheets are added (ie, the obtained gas-sensitive material is SnO2 / CNFs).
[0095] Comparative Example 2
[0096] The method described in Example 1 is followed, except that in step (4), SnCl2·2H2O is not added (ie, the obtained gas-sensitive material is MoS2 / CNFs).
[0097] Test Example 1
[0098] The MoS2 / PVP / PAN nanofiber membrane and SnO2 / MoS2 / CNFs gas-sensitive material prepared in Example 1 were tested using a scanning electron microscope, wherein the scanning electron microscope used was a field emission scanning electron microscope JEOL IT-800 produced by JEOL Ltd. The test results are shown in FIG. Figure 1 shown. Figure 1 In the figure, (ab) are scanning electron microscope images of MoS2 / PVP / PAN nanofiber membrane at different magnifications, (c) is a scanning electron microscope image of SnO2 / MoS2 / CNFs gas-sensitive material, and (d) is an electron microscope image of pure SnO2 nanoparticles on SnO2 / MoS2 / CNFs gas-sensitive material.
[0099] Figure 1 The results of (ab) show that the fibers after spinning are uniform and smooth, with a diameter of about 170 nm. Figure 1 (c) shows that the carbon nanofibers loaded with SnO2 in situ and calcined still present a three-dimensional network structure that intersects each other. After the carbon nanofibers are loaded with SnO2 nanoparticles, the surface is rough and porous, which greatly increases the specific surface area and active sites of the gas-sensitive material, which is beneficial to the gas adsorption performance of the gas-sensitive material. Figure 1 (d) It can be seen that the SnO2 nanoparticles are uniform in size.
[0100] Test Example 2
[0101] In this test example, in the sensitivity test, the sensitivity S of the gas sensor is defined as Δ R / Ra, Ra is the initial resistance of the gas sensor in argon, Rg is the resistance value of the gas sensor in the gas to be measured, and ΔR is the difference between the resistance of the gas sensor in argon and the resistance in the gas to be measured |Rg-Ra|.
[0102] Gas sensing performance test: The test equipment used is the CGS-8 intelligent gas sensitive analysis system and DGD-V digital dynamic gas distribution system produced by Beijing Zhongju Hi-Tech Technology Co., Ltd.
[0103] 1. Sensitivity test
[0104] (1) The sensitivity of the gas sensor prepared in Example 1 was tested at different hydrogen concentrations (1000-10000 ppm), wherein the operating temperature of the gas sensor was 120° C. The test results are as follows: Figure 2-3 shown.
[0105] Figure 2-3 The results show that as the H2 concentration increases, the sensitivity also increases. When the concentration increases, the upward trend of the sensitivity curve gradually slows down, but it is still rising, indicating that the gas sensor has the characteristics of large range and high precision. The sensitivity of the gas sensor to 1000ppm, 1500ppm, 2000ppm, 2500ppm, 3000ppm, 3500ppm, 4000ppm, 4500ppm, 5000ppm, 5500ppm, 6000ppm, 6500ppm, 7000ppm, 7500ppm, 8000ppm, 8500ppm, 9000ppm, 9500ppm and 10000ppm H2 gas can reach 26.3%, 31.5%, 37%, 41.1%, 45.3%, 47.8%, 50.6%, 53.1%, 54.8%, 56.6%, 58.4%, 60%, 61.2%, 62.5%, 63.5%, 64.7%, 65.7%, 66.6% and 67.2% respectively.
[0106] (2) The sensitivity of the gas sensors prepared in Examples 2-5 and Comparative Examples 1-2 at different hydrogen concentrations was tested, wherein the operating temperature of the gas sensors was 120° C. The test results are shown in Table 1 below.
[0107] Table 1
[0108]
[0109]
[0110] It can be seen from Table 1 that the sensitivity of the gas sensor is improved by compounding SnO2 and MoS2.
[0111] (3) Repeat the test of the resistance response of the gas sensor prepared in Example 1 to 10000 ppm H2 gas, wherein the temperature of the gas sensor is 120°C. The test results are as follows: Figure 4 shown.
[0112] Depend on Figure 4 It can be seen that the gas sensor has almost no change in performance after 17 consecutive repeated gas-sensing tests, which proves that the gas sensor has good stability.
[0113] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing a gas-sensitive material, characterized in that: The method comprises the following steps: (1) mixing polyvinyl pyrrolidone, polyacrylonitrile, MoS2 and N,N-dimethylformamide to obtain a spinning solution; (2) obtaining a nanofiber membrane by electrospinning the spinning solution; (3) in situ synthesis of SnO2 nanoparticles on the nanofiber membrane using a solvothermal method; (4) The SnO2-loaded nanofiber membrane obtained in step (3) is pre-oxidized and then calcined.
2. The method according to claim 1, characterized in that In step (1), the concentration of polyvinyl pyrrolidone in the spinning solution is 10 to 40 g / L; Preferably, in step (1), the concentration of polyacrylonitrile in the spinning solution is 60 to 80 g / L; Preferably, in step (1), the concentration of MoS2 in the spinning solution is 0.3 to 0.8 mol / L.
3. The method according to claim 1, characterized in that In step (2), the conditions for electrospinning include: positive voltage of 15 to 20 kV, negative voltage of -1 to -3 kV, flow rate of 0.4 to 0.6 mL / h, temperature of 50 to 70° C., and receiving distance of 10 to 14 cm.
4. The method according to claim 1, characterized in that Step (3) includes: dissolving a tin salt in an organic solvent to obtain a precursor solution; The nanofiber membrane is acidified, then mixed with the precursor solution, and then kept warm at 120-180° C. for 8-12 hours.
5. The method according to claim 4, characterized in that In the precursor solution, the concentration of tin salt is 0.5-2 mol / L; Preferably, the tin salt is SnCl2·2H2O and / or SnCl4·5H2O; Preferably, the organic solvent is selected from at least one of ethanol, ethylene glycol and propanol; Preferably, the acidification treatment is performed using a mixed acid solution, wherein the mixed acid solution is obtained by mixing concentrated sulfuric acid and concentrated nitric acid.
6. The method according to claim 1, characterized in that In step (4), the pre-oxidation conditions include: temperature of 260-300° C. and time of 20-40 min.
7. The method according to claim 1, characterized in that In step (4), the calcination is a two-stage calcination process, wherein the temperature of the first stage is 230-270° C., and the temperature of the second stage is 520-580° C.; Preferably, the heating rate in the first stage is 0.5-3°C / min, and the holding time is 40-80min; Preferably, the heating rate in the second stage is 1-3°C / min, and the holding time is 150-200min.
8. A gas-sensitive material prepared by the method according to any one of claims 1 to 7.
9. A gas sensor, characterized in that: The gas sensor comprises a gas-sensitive material prepared by the method according to any one of claims 1 to 7.
10. Use of the gas sensitive material prepared by the method according to any one of claims 1 to 7 or the gas sensor according to claim 9 in hydrogen detection.
Citation Information
Patent Citations
Application of semiconductor oxide ultrafine nanoparticles in cataluminescence sensor, and preparation method of semiconductor oxide ultrafine nanoparticles
CN102181286A
Graphene / molybdenum disulfide compounding-based gas sensitive material and preparation method thereof
CN104792830A
Hierarchical tin oxide nanosheet / silicon carbide nanofiber and preparation method thereof
CN104846624A
Preparation method of nano-composite membrane electrode material
CN104868100A
Preparation method and application of cobaltosic oxide and tin oxide composition nanowires
CN110624558A